The Use of Google Classroom in Facial Skin Care Courses with Technology: Penggunaan Google Classroom pada Mata Kuliah Perawatan Kulit Wajah dengan Teknologi - Putri, Hasri Mutiara; Arum, Aniesa Puspa; Ambarwati, Neneng Siti Silfi (Politeknik Harapan Bangsa Surakarta, 2021)
Learning outcomes are a learning carried out by someone after Â going through the process of learning activities, which uses an assessment tool prepared by the teacher, such as an evaluation test that includes cognitive, affective and psychomotor aspects. This study aims to determine the relationship between student interest in the use of Google Classroom with learning outcomes of facial skin care with technology. This research is a quantitative research with a survey method with a sample of 65 students of the Cosmetology Education study program batch 2020. The data for the X variable (student interest in using Google Classroom) was obtained by distributing questionnaires with a Likert scale. Meanwhile, the Y variable data (Learning Results of Facial Skin Care with Technology) was obtained from Form 06. The results of the analysis with product moment correlation showed that there was no positive and significant relationship between students' interest in learning outcomes of facial skin care with technology. Based on the calculations obtained a significance value of 0.274 which means it is greater than 0.05. So it can be concluded that Ho which reads: